Lower calyceal and renal pelvic stones in preschool children: A comparative study of mini‐percutaneous nephrolithotomy versus extracorporeal shockwave lithotripsy. (13th May 2016) - ElSheemy, Mohammed S; Daw, Kareem; Habib, Enmar; Aboulela, Waseem; Fathy, Hesham; Shouman, Ahmed M; El Ghoneimy, Mohamed; Shoukry, Ahmed I; Morsi, Hany A; Badawy, Hesham
Abstract : Objectives: To compare outcomes of the mini‐percutaneous nephrolithotripsy technique and extracorporeal shockwave lithotripsy for lower calyceal and renal pelvic stones in preschool children. Methods: From January 2010 to December 2014, single renal pelvic or lower calyceal calculi 10–25 mm in size in children (age ≤6 years) treated by either extracorporeal shockwave lithotripsy (64 patients) or the mini‐percutaneous nephrolithotripsy technique (54 patients) were included. Extracorporeal shockwave lithotripsy was carried out by using a Dornier electromagnetic lithotripter. The mini‐percutaneous nephrolithotripsy technique was through 14‐Fr renal access using a 9.5‐Fr semirigid ureteroscope with holmium:yttrium aluminium garnet lithotripsy. The two study groups were compared using Mann–Whitney, χ 2 ‐test or Fisher's exact test. Results: Stone parameters were similar in the mini‐percutaneous nephrolithotripsy technique and extracorporeal shockwave lithotripsy groups in all patients, and in the pelvic (39 Miniperc, 52 extracorporeal shockwave lithotripsy) and lower calyceal (15 Miniperc, 12 extracorporeal shockwave lithotripsy) subgroups. Stone‐free rates in the mini‐percutaneous nephrolithotripsy technique and extracorporeal shockwave lithotripsy groups were 88.9% versus 43.8% ( P < 0.001) and 94.4% versus 81.2% ( P = 0.032) after first and last sessions, respectively. In the renal pelvis, they were 87.2% versus 50% ( P < 0.001) and 94.9% versus 84.6% ( P = 0.179), whereas in the lower calyx, they were 93.3% versus 16.7% ( P < 0.001) and 93.3% versus 66.7% ( P = 0.139) after first and last sessions, respectively. Retreatment rates in the mini‐percutaneous nephrolithotripsy technique versus extracorporeal shockwave lithotripsy were 7.4% versus 50% ( P < 0.001), 7.7% versus 46.2% ( P < 0.001), and 6.7% versus 66.7% ( P = 0.003) in all patients, renal pelvic and lower calyceal stones, respectively. No significant difference was found in complications ( P = 0.521). Auxiliary procedures were required in 9.4% and 1.9% of children in the extracorporeal shockwave lithotripsy and mini‐percutaneous nephrolithotripsy technique groups, respectively. Conclusions: The mini‐percutaneous nephrolithotripsy technique has significantly higher stone‐free rates than extracorporeal shockwave lithotripsy for renal pelvic and lower calyceal stones (10–25 mm), with a lower retreatment rate and without a significant increase in complications.